Genomic research and the cancer clinic: uncertainty and expectations in professional accounts. Issue 2 (3rd April 2019) - Kerr, Anne; Swallow, Julia; Chekar, Choon Key; Cunningham-Burley, Sarah
Abstract : This paper explores clinicians' and scientists' accounts of genomic research in cancer care and the complexities and challenges involved with delivering this work. Contributing to the sociology of (low) expectations, we draw on sociological studies of uncertainty in medicine to explore their accounts of working with uncertainty as part of the management of patient and institutional expectations. We consider their appeals to the importance of modest inquiry and framing of the uncertainties of genomic medicine as normal and at times welcome as they sought to configure professional autonomy and jurisdictions and cultivate an experimental ethos amongst their patients. We argue that these types of uncertainty work [Star, S. L. 1985. "Scientific Work and Uncertainty." Social Studies of Science 15 (3): 391–427] are a key feature of managing expectations at the intersections of genomic research and clinical care.